PENERAPAN MODEL KONSELING SPIRITUAL TEISTIK UNTUK MENINGKATKAN SPIRITUAL WELL BEING ORANG TUA ABK DI SLB NEGERI HARURU - Juliana Tuhumury (IAKN Ambon, 2022)
Being a parent with a child with special needs puts pressure on them because they have to pay more attention, not the same as normal children in general and often this pressure has the impact of psychological distress on parents. This also happened to parents of children with special needs at the Haruru State SLB. Psychological distress for parents of children with special needs greatly impacts various aspects, one of which is spiritual well being. Based on research conducted by several parents of children with special needs, they have low spiritual well being, therefore it is necessary to have therapy to improve their spiritual well being. The counseling method used to improve low spiritual well being is spiritual counseling with ten counseling sessions. There were 6 participants involved and all of these participants attended counseling until the last session. The results of the study show that theistic spiritual counseling is effective in improving the spiritual well being of parents of children with special needs who experience psychological distress. This can be seen from the sig value of 0.061 that there were changes before and after counseling was carried out for parents of children with special needs.